The Role of Education in Human Development in Iraq for the Period 1980-2012 - Mahmood, Sabah Faihan; Mahmood, Yassen Taha (Journal of University of Human Development, 2016)
Human Development aims to enlarge choices in front of people by improving the level of health, education, and income; this means that this process will upgrade both the economic and social development.In other words, human development aimes to raise the average of age and this requires the advancement of the health aspect, raise the level of knowledge and this requires the advancement of the educational aspect of all kinds., and raise the standard of living, and this requires the advancement of the economic aspect by providing the necessary jobs and promote economic activities. The study focus on the relationship between education and human development which has great importance as a mean to determine the impact of education on human development. The research seeks to achieve a set of objectives, including: Review the concept of human development and its basic elements, shed light on the reality of development in Iraq and follow the path of its development, and find out the role of education in influencing human development through the changes taking place in it and its impact on increase or decrease human development index during the period of the research. The research found set of results, the most important were the important effect of the education index on the level of human development index represented by HDI. Iraq had a good educational system in the eighties and nineties, reaching good education index value for the year (1990) which was (0.890), making the human development index in Iraq in the highest level and the value of the Human Development Index (0.759) in the first report issued by the United Nations in the year (1990). when the education index fall back there was negatively impact on the value of human development index in Iraq Directory, so when the education index value became (0.721) , the value of the Human Development Index was (0.590) in the year 2011 . This means that the value of the human development index decrease in recent years, although of improvement in the level of health, and the average per capita GDP in Iraq, and this illustrates the significant role of education on the human development process.